A modified droop controller for parallel operation of single-phase inverters in Islanded microgrid - Usman Bashir, Tayab (Intelligent Network and Systems Society, 2017)
Conventional droop control is a basic control strategy for power sharing in islanded microgrid applications. This strategy has several limitations, such as low transient response, frequency and voltage deviations. This paper presents a modified droop control method for the proper operation of parallel-connected inverters in islanded microgrid. The proposed method is able to improve transient response and achieved higher output power without voltage and frequency deviations by introducing a power derivative term into a conventional droop method. A new method of average power computation is proposed which significantly reduces the delay encountered in conventional approaches and provides the power signal without DC components. The simulation was developed in MATLAB/Simulink to verify the effectiveness of the modified droop control scheme. Based on the results, it can be concluded that the modified droop control strategy improves the performance of parallel-connected power electronic inverters in an islanded microgrid as compared to conventional droop control strategy.